Rancang Bangun Aplikasi M-Sembako Dalam Peningkatan Integrasi Rantai Suplai Digital UKM di Kota Batam - Amrizal Amrizal; Tukino Tukino (Prosiding, 2020)
One of the benefits of information technology in developing SMEs for entrepreneurs is to accelerate business processes, where the use of information technology is done because technology is able to overcome the problem of distance and time needed in a business process. Where in the implementation of its work is still simple in the form of application manuals and assisted by Microsoft Word and Microsoft Excel for documents. This resulted in the supply chain management process being ineffective and inefficient. As a solution to the problem, the author makes an application and integrated supply chain system based on the car in the M Sembako case study. The research method used is a system development approach which consists of a feasibility study and system design. The results obtained from research in the form of supply chain information systems using Android-based Programming on SMEs in Batam where this system can be more easily implemented and more easily understood by users so that it can produce information that is fast, precise and accurate.